Kinerja Pengawas Di Sekolah Dasar Integral Hidayatullah Putri Hijau Kabupaten Bengkulu Utara - Fajar Cici Mulyana, Ahcmad; Sumarsih (UNIVERSITAS BENGKULU, 2024)
The general purpose of this research is to describe the performance of supervisors at the Hidayatullah Putri Hijau Integral Elementary School, in North Bengkulu Regency. The specific aim of this research is the performance of supervisors in teacher academic supervision. managerial supervision of the school principal, evaluation of the results of the implementation of the supervision program and follow-up to the results of the evaluation of the implementation of the supervision program. The method in this research is descriptive qualitative. The research subject was the supervisor of Elementary School. Data collection techniques use observation, interviews and documentation. Data analysis techniques go through the stages of data reduction, data presentation, verification and drawing conclusions. The results of the research show that the performance of school supervisors needs to be substantially improved in the areas of supervision, evaluation and follow-up of supervisory programs to further support the development of teacher and school principal competency. The general conclusion in this research is that the performance of school supervisors still needs to be improved in various aspects to support the development of teacher and school principal competencies more effectively. Suggestions for supervisors to improve their abilities in planning, organizing, budgeting and evaluating supervisory programs.